Quedas sofridas por moradores de uma instituição de longa permanência para idosos - Bianco, Viviane da Silva (2008)
The present aging scenario brings about the need to adapt society to meet particularities of the individuals involved in this stage of the vital cycle. In Brazil the aging population has been growing considerably and the alternatives of assistance and resources for such population are still deficient. Families are seldom prepared to face the aging process of their relatives and, especially because of difficulties related to finances and home care, they eventually choose institutions. Living at a long term care institution can be the very elder s choice seeking to preserve their selves and their belongings so as to keep their life history alive. The natural aging process brings along numerous changes, with the loss or slowering of body response. Pathology prevention and symptom minimization allow aging people to attain a better quality of life, and various segments are assigned this task geriatric and gerontologic multidisciplinary teams, among them. Among the problems aging people face, the falls are relevant and worrying because of their consequences. Because falls are frequent and can bring injuries to the elderly, the present study gathered institutional fall protocols from the residents of the Residencial Israelita Albert Einstein who were involved in falls during a pre-established period and analyzed the number of falls, the form of their occurrence and who were involved in this type of event with the purpose of preventing new episodes as well as providing post-fall assistance